Multi-objective polymer single screw extruder optimization - Rocha, Ana Maria A. C. (2022)
The optimal design of a polymer single screw extruder may involve various conflicting performance objectives and depends on operating and geometrical parameters. In this work, five bi-objective problems are analysed where one of the most relevant performance objectives, the mass output, is considered in all problems. For simplicity purposes, only the operating parameters are optimized being the geometrical parameters assumed to be fixed. The optimal solution set of each problem is compared with the corresponding two-dimensional projection of the Pareto front obtained when the six objectives are optimized simultaneously. A weighted Tchebycheff scalarization algorithm is implemented based on the simulated annealing method to obtain the Pareto front of the multi-objective optimisation problems.